A construção do mercado de cafés certificados e sustentáveis da Utz Certified no Brasil: as práticas e os arranjos de mercado - Leme, Paulo Henrique Montagnana Vicente (2015)
This study used the theoretical framework of the Actor Network Theory (ANT) and Constructivist Market Studies (CME) to analyze how market practices interacted in building market arrangements over Utz Certified market development process in Brazil. The practices-arrangements-translations interaction in a process of marketization are the theoretical core of the CME. In studying the formation of markets, there are several possible arrangements, in products, agencies and market meetings, or studying the formation of prices and the design, implementation and maintenance of markets. The focus is on the practices and relationships where human and nonhuman actors work together. Kjellberg and Helgesson (2006, 2007b) propose a conceptual analytical framework for the study of markets based on market practices (exchange, representational and normalizing practices). We propose in this thesis an analytical framework for the Utz Certified market in Brazil correlating market practices with market arrangements in a longitudinal process. As a research strategy it was adopted the case study. The methodology involved a historical reconstruction of the Utz Certified market with document analysis and semi-structured interviews with selected stakeholders. The results point towards an integrated view of market practices and market arrangements. By analyzing market practices, we can identify and categorize the processes of framing and overflow. This perspective allows us to understand the different market settings over time. By applying the analytical framework as lens in the case study it was possible to select specific translation moments that resulted in different market configurations. Through the historical reconstruction of the certification, the analysis of market contexts, and also from the testimony of local actors responsible for organizing the Utz in Brazil, it was possible to identify the main market practices adopted by the actors involved in the organization and the market design. It was highlighted the role of market building practices as important mediating instances to build market arrangements and the modification and consolidation of exchange, representational and normalizing practices. The building practices and market practices have shown how they interact in a temporal and longitudinal process in the event of translations, causing market overflows, with consequent market framing mediated by new building practices and market practices in an ongoing process.